Late Antique textiles from Egypt in the Ny Carlsberg Glyptotek, Copenhagen - Brøns, Cecilie; Berghe, Ina Vanden; Skals, Irene (Archaeological Textiles Review, 2019)
The Ny Carlsberg Glyptotek (NCG) possesses a small collection consisting of 13 fragments of Late Antique textiles from Egypt, possibly from the site of Akhmim. The collection primarily consists of cut-outs of decorative elements. The collection has until now not received much attention nor been thoroughly analysed. The present study seeks to remedy this neglect by performing fibre and dye analyses as well as including archival material from the museum collections.